Regresi Model Data Panel Efek Tetap dengan Metode Within Group pada Data Indeks Pembangunan Manusia Provinsi Sulawesi Selatan - Andi Sitti Fahmi Riyanti Hufaini; Raupong Raupong; Nirwan Ilyas (Hasanuddin University, 2020)
This research aims to describe the parameter estimation of the regression model on the panel data by approaches of Fixed Effects Model with within a group method. This research aims to determine the factors that influence the Human Development Index in South Sulawesi Province in 2011-2017 using Panel Data Regression Analysis. The regression model was obtained from the maximum likelihood estimation using within group approach using a mean for each independent variable and the dependent variable to find out the intercept differences in each city or cross-section that explains the effect of regional differences and to find out the intercept differences for cross sectional or time series. The results showed that the average length of the school variable (????1) and life expectancy variable (X2) significantly affects the Human Development Index (Y) in the Province of South Sulawesi in 2011-2017.